COPE network coding based on broadband Ad hoc network - Li, Xuwen (My University, 2020)
In the traditional communication network, the transmission of data is realized by the storage and forwarding of the node. Since the node can only send one packet at a time, the remaining packets must be queued, resulting in slow network transmission rate. When the network load increases, network congestion occurs. In 2000, the concept of network coding was firstly proposed. It allows intermediate nodes to participate in the coding process. However, the coding and decoding operation makes the complexity higher. The wireless network coding technology COPE combines wireless network with network coding, which solves the problem. This paper studies the Ad hoc network and uses its advantages. The routing protocol of Ad hoc network is analyzed, and the AODV routing scheme has better performance. It uses a broadband Ad hoc network, and defines the RF front-end and air interface physical interconnection layers. The system scheme was optimized, and certain improvements were made in the routing scheme strategy selection. This paper briefly introduces the development of network coding, the principle and application, and details the principle and algorithm of wireless network coding COPE scheme. The COPE scheme adds a coding layer between the IP layer and the MAC layer. The sending node analyzes the data packets in its output queue, determines which packets will be encoded according to the information of the next hop node, and then send the encoded packet. This research proposes two topological solutions for specific system solutions, and designs the COPE network coding, and combines routing protocols to achieve a variety of topologies of multi-hop Ad hoc network. Finally, the study simulates a network with specific topology based on the simulation software OPNET, and obtains good experimental results. Analyze the advantages and disadvantages of the COPE solution. Experiments show that the system can achieve better throughput and lower system latency.